(untitled) (Mustansiria Dental Journal, 2018)
One of the most important practical deficiencies of present denture base materials is fracture, therefore many attempts have been made to reinforce of the repaired denture base resin, a desirable objective for this service is to obtain optimum strength for repair, which can be achieved by making available a good bound between original and repair materials. The present study was carried out to evaluate and compare the effect of different surface treatments (monomer, acetone, combination monomer + acetone) on the transverse strength of acrylic denture base. Seventy (70) specimens were prepared from pink heat-cure acrylic resin of which (10) specimens were considered a control group. The remaining specimens were divided into two main groups (30specimens repaired by Ivomat and 30 specimens repaired by air method). The joint treated before cold-cured acrylic resin was applied to the joint space. Specimens were repaired by cold-curing resin (major). Then they were stored in distilled water at (37 Co) for (48) hours. These were subjected to three-point loading testing machine to determine the transverse strength. The results showed that air cured acrylic resin has significant lower transverse strength than Ivomat cured acrylic resin also show that the specimen treated with (Acetone + monomer) have a higher transverse strength. Finally, it can be concluded that curing methods and surface treatment will improve transverse strength of the repaired acrylic denture base re